"The Cave", by José Saramago: the dream of Cipriano - Bautz, Diego Kauê (Revista Desassossego, 2022)
This work intends to analyze the novel The Cave (2000), by José Saramago, to reflect on how the characters working are objectified by the Center, a kind of shopping mall of monstrous proportions that controls the entire narrative space. For this, the study recovers several moments of the novel, but it focuses, mainly, on one of the scenes in which the potter Cipriano, the protagonist of the work, dreams of a new oven that would adapt him to the demands of the Center. In this way, based on Jung's studies (2000), Cipriano's dream was perceived as the apex of the character's crisis, as it expresses, first, Cipriano's frustration with the loss of his workforce and, then, the recognition of his status as a disposable worker; which subsequently conditions him to break with the way of life imposed by the Center, whose values are guided by the ideals of efficiency and productivity.